A halogen perovskite-based heterojunction composite material and its synthesis method and application
By constructing a Z-type heterobonding composite material of halogen perovskite and selenium bismuth oxide, the problems of instability and insufficient visible light absorption of traditional halide perovskite materials in high humidity environments are solved, and efficient pollutants are achieved Degradation and stability improvement.
Patent Information
- Application Number
- CN202411192284.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-28
AI Technical Summary
Traditional halide perovskite materials are unstable and toxic in high humidity environments, and their photocatalytic efficiency is limited by the problem of insufficient absorption of visible light.
By constructing a Z-type heterobonding composite material of halogen perovskite and selenium bismuth oxide, the interlayer electrostatic action and built-in electric field transfer are used to improve the interface charge separation efficiency, and the Cs3Bi2I9/Bi2O2Se composite material is prepared by hydrothermal reaction method to enhance light Catalytic activity and stability.
The interface charge separation efficiency is improved, the visible spectrum coverage of photocatalytic materials is expanded, the degradation efficiency of pollutants is significantly improved, and the stability of the material is maintained in the aqueous phase, and the reusability is achieved.
Smart Images

Figure CN118698567B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysts, and in particular relates to a halogen perovskite-based heterojunction composite material and a synthesis method and application thereof. Background Art
[0002] In recent years, lead-free halide perovskite materials have shown promising performance, especially in solar cell applications. These materials are ideal candidates for photocatalytic applications due to their large absorption coefficients resulting from favorable band gaps, point defects, grain boundaries, and long electron-hole diffusion lengths, which reduce the recombination of electron-hole pairs. In addition, the synthesis of these materials is easily reproducible and inexpensive. In the past, lead halide peroxides showed high solar energy harvesting efficiencies. However, this material exhibits instability, especially in high humidity environments, and Pb 2+ As bioavailable cations may be leached, this makes lead-based materials toxic and unsuitable for wastewater treatment. In contrast, inorganic peroxide materials have much better stability, especially bismuth-based halide perovskites have attracted much attention because they solve the stability and toxicity issues associated with lead-based materials.
[0003] One of the means to improve the photocatalytic activity is to construct a heterojunction by combining bismuth-based halide perovskites with traditional bismuth oxyhalide photocatalysts (BiOX, X=F, Cl, Br). Anchoring bismuth-based halide perovskites on bismuth oxyhalide photocatalysts can promote charge separation and transport by arranging the energy bands between the material interfaces. On the other hand, the different band gaps, layered structures and special internal electrostatic fields of bismuth oxyhalide photocatalysts are different due to the different halogens, which is beneficial to improve the chemical interaction between the material and the pollutants. In addition, loading bismuth-based halide perovskite particles on the surface of bismuth oxyhalide materials is expected to be more stable in photoreactions, which can solve the instability to water. However, traditional bismuth oxyhalide photocatalysts have insufficient visible light absorption, such as the light absorption cutoff edge of BiOCl is about 380nm, and the light absorption cutoff edge of BiOBr is about 450nm, which indicates that the composite materials cannot effectively utilize more visible light, resulting in low photocatalytic efficiency. Compared with bismuth oxyhalides, the halogen elements in bismuth oxyselenide (Bi2O2Se) materials are replaced by VIA group elements. Therefore, the valence band and conduction band characteristics of the photocatalyst are mediated by selenium groups with different orbitals, which is beneficial to improve the optical absorption of the material. Interlayer electrostatic interaction replaces [Bi2O2] n 2n+ Layer and [Se] n 2n- The van der Waals forces between the layers are beneficial to accelerate the effective separation of light carriers.
[0004] Environmental issues and energy crisis have become major challenges in the past few decades. Meanwhile, the rapid population growth and increasing industrial activities have caused adverse effects on the environment, especially water pollution. In this context, people are paying more and more attention to adopting sustainable and eco-friendly energy to eliminate organic pollutants and protect water resources. Among the existing methods, semiconductor photocatalysis technology has been widely studied by researchers in recent decades due to its attractive features such as environmental compatibility, high efficiency, low cost, and the use of clean and renewable energy to degrade organic dyes and purify water.
[0005] Cesium bismuth iodide (Cs3Bi2I9) is a low-toxic and stable halogen perovskite with a narrow band gap (~1.9 eV) and a relatively negative conduction band (~-1.1 eV) that allows good visible light capture and strong reduction ability, making it a potential photocatalyst for the degradation of pollutants. These dual-base catalysts have become "green materials" due to their safety, non-toxicity, low cost, and easy availability, and are widely used in medicine, catalysts, batteries, and other fields. Cs3Bi2I9 is composed of the same perovskite-like fragments with the general formula A3Bi2I9, with alternating edges [BiI6] 3- Octahedral layer, the gaps of which are composed of Cs + Cation filling. This adjustable structure and morphology have a great influence on its intrinsic electronic and optical properties, which can be used in photocatalysis. Excellent photoluminescence intensity suppression and significantly lower toxicity than lead halide make it possible to composite with other semiconductor materials.
[0006] Bismuth oxide selenium (Bi2O2Se) is a semiconductor material with a zipper-like layered structure. Its interlayer interaction is electrostatic, which is different from the van der Waals force of other two-dimensional materials. 2+ The layers are stacked in reverse along the c-axis direction, Se 2- The ions are arranged vertically along the c-axis, interspersed in [Bi2O2] 2+ Between the layers. Due to its special structure and excellent photoelectric and thermoelectric properties, Bi2O2Se has been widely used in research fields such as photoelectric devices and thermoelectric materials. Bi2O2Se has the characteristics of ultra-high carrier mobility, high light absorption rate and light response ability, environmental stability, non-toxicity, and low raw material cost.
[0007] However, both single cesium bismuth iodide and bismuth selenide oxide are limited by their rapid charge recombination. Constructing a Z-type heterojunction can drive the transfer of photogenerated carriers through the built-in electric field, improve the quantum yield, while maximizing the retention of electrons and holes with strong redox capabilities, promoting efficient removal of pollutants. Summary of the invention
[0008] The purpose of the present invention is to provide a method for synthesizing a halogen perovskite-based heterojunction composite material to prepare a heterojunction composite material with higher interface charge separation efficiency, simple preparation method, better stability, reusability, and piezoelectric photocatalytic degradation of organic pollutants.
[0009] Another object of the present invention is to provide a halogen perovskite-based heterojunction composite material.
[0010] The third object of the present invention is to provide an application of a halogen perovskite-based heterojunction composite material.
[0011] The technical solution of the present invention is: (one)
[0013] A method for synthesizing a halogen perovskite-based heterojunction composite material comprises the following steps:
[0014] A. Mix appropriate amounts of BiI3 and CsI into a certain volume of N,N-dimethylformamide, heat the mixture at a certain temperature under magnetic stirring until N,N-dimethylformamide is completely evaporated, centrifuge with toluene to remove the N,N-dimethylformamide residue, and dry to obtain bright red powder Cs3Bi2I9 for use;
[0015] B. Ultrasonic disperse a certain mass of Cs3Bi2I9, ammonium bismuth citrate and sodium selenite in ultrapure water respectively, and mix the three under stirring at room temperature; then slowly add an appropriate amount of alkali (such as sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium hydroxide) to adjust the pH value to 11.0-13.0, and slowly transfer to a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction after continuous stirring. After the reactants are cooled, filter, wash with ultrapure water and anhydrous ethanol, and dry to obtain the heterojunction composite material Cs3Bi2I9 / Bi2O2Se.
[0016] As a further improvement of the present invention, in step A, the ratio of the amounts of BiI3, CsI and N,N-dimethylformamide is 1-2:1.5-3:150-300.
[0017] As a further improvement of the present invention, in step A, the heating temperature is 60-80°C.
[0018] As a further improvement of the present invention, in step A, the drying temperature is 60-80° C., and the drying time is 12-24 hours.
[0019] As a further improvement of the present invention, in step B, the mass ratio of Cs3Bi2I9, ammonium bismuth citrate and sodium selenite is 1:1.2-3.6:0.2-0.7.
[0020] As a further improvement of the present invention, in step B, the temperature of the hydrothermal reaction is 180-200° C., and the time of the hydrothermal reaction is 20-24 h.
[0021] As a further improvement of the present invention, in step B, the drying temperature is 60-80° C., and the drying time is 12-24 hours.
[0022] The present invention combines halogen perovskite and bismuth selenide oxide materials. The interlayer electrostatic effect and the existence of the heterojunction effectively improve the interface separation efficiency, so that the halogen perovskite-based material can efficiently degrade pollutants under the action of visible light irradiation and has the characteristics of good stability in the aqueous phase. (two)
[0024] A halogen perovskite-based heterojunction composite material is prepared by the above-mentioned synthesis method of the halogen perovskite-based heterojunction composite material.
[0025] Among them, the presence of Cs3Bi2I9 reduces the recombination of electron-hole pairs and greatly improves the sunlight capture efficiency, while the introduction of Bi2O2Se solves the problem of instability of traditional halogen perovskite materials in aqueous phase to a certain extent, improves the stability of the material, and avoids the problem of insufficient light absorption of composite materials caused by the use of traditional bismuth oxyhalide materials. (three)
[0027] Application of a halogen perovskite-based heterojunction composite material in visible light photocatalytic degradation of pollutants in wastewater.
[0028] Further, pollutants in wastewater include but are not limited to atrazine, bisphenol A, carbamazepine, atrazine, tetracycline, and rhodamine b. Preferably, Cs3Bi2I9 / Bi2O2Se of the present invention has an exceptionally excellent degradation effect on atrazine under photocatalytic conditions. On the one hand, under visible light irradiation, the photocatalytic material Cs3Bi2I9 / Bi2O2Se is photoexcited to generate photogenerated electrons and photogenerated holes under visible light irradiation, and the matching energy level position enables the photogenerated electrons of the Bi2O2Se conduction band to be transferred across the heterojunction interface to the Cs3Bi2I9 valence band. This Z-type charge transfer mechanism not only promotes carrier separation, but also retains strong redox ability. On the other hand, the built-in electric field generated between the two under electrostatic interaction further induces electrons to migrate from Bi2O2Se to Cs3Bi2I9, and the electron cross-interface transfer will effectively inhibit the recombination of electron-hole pairs, thereby significantly improving the charge separation efficiency. Finally, the pollutants are oxidized by surface active oxygen or hydroxyl groups and holes, and finally generate water and carbon dioxide.
[0029] The beneficial effects of the present invention are:
[0030] The present invention composites Cs3Bi2I9 and Bi2O2Se by constructing a heterojunction to construct a perovskite photocatalytic nanocomposite material, Cs3Bi2I9 / Bi2O2Se, which has a stronger interface carrier separation ability, an absorption range covering the entire visible spectrum, and a higher catalytic activity. Cs3Bi2I9 avoids the stability and toxicity problems associated with traditional lead-based materials, and has a narrow band gap, but the charge separation efficiency of a single material is low; Bi2O2Se has better optical absorption than traditional bismuth oxyhalide materials, and bismuth-based halide perovskite particles loaded on the surface of bismuth oxyhalide materials are expected to be more stable in photoreactions, which can solve the instability in the aqueous phase. Cs3Bi2I9 and Bi2O2Se are composited to successfully achieve the separation of photogenerated electron-hole pairs in the Cs3Bi2I9 / Bi2O2Se composite photocatalytic nanomaterial at the heterojunction interface, avoiding the electron-hole recombination problem in the band gap of a single nanomaterial. [BiI6] 3- and [Bi2O2] 2+ The electrostatic effect caused by the interlayer arrangement makes the two closely combined, which can accelerate the migration and separation of photogenerated charges. The construction of the heterojunction more effectively enhances the charge separation and electron transfer at the heterojunction interface, greatly improving the photocatalytic activity. Ultimately, the Cs3Bi2I9 / Bi2O2Se photocatalytic system achieves effective pollutant degradation and has the characteristics of good stability and reusability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of Cs3Bi2I9 / Bi2O2Se prepared in Example 1 of the present invention;
[0032] Figure 2 The ultraviolet diffuse reflectance spectra of Cs3Bi2I9 / Bi2O2Se, Cs3Bi2I9, and Bi2O2Se prepared in Example 1 and Comparative Examples 1 and 2 of the present invention;
[0033] Figure 3 Fourier diffuse reflectance infrared spectra of Cs3Bi2I9 / Bi2O2Se, Cs3Bi2I9, and Bi2O2Se prepared in Example 1 and Comparative Examples 1 and 2 of the present invention;
[0034] Figure 4 This is a performance comparison chart of photocatalytic degradation of atrazine by Cs3Bi2I9 / Bi2O2Se, Cs3Bi2I9, and Bi2O2Se prepared in Example 1 of the present invention and Comparative Examples 1 and 2;
[0035] Figure 5 This is a degradation diagram of the reusability experiment of photocatalytic degradation of atrazine by Cs3Bi2I9 / Bi2O2Se prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below through the accompanying drawings and specific embodiments.
[0037] Embodiment 1,
[0038] A method for synthesizing a halogen perovskite-based heterojunction composite material comprises the following steps:
[0039] A. Mix 1.2 mM BiI3 and 1.8 mM CsI in a round-bottom flask containing 15 mL (180 mM) N,N-dimethylformamide. Heat the mixture at 60 °C under magnetic stirring at 600 r / min until the solvent N,N-dimethylformamide is completely evaporated. Then, centrifuge and wash it three times with toluene to remove the N,N-dimethylformamide residue. Dry it in an oven at 60 °C for 12 h to obtain a bright red powder Cs3Bi2I9 for use.
[0040] B. Disperse 1.0 g of Cs3Bi2I9, 1.808 g of ammonium bismuth citrate and 0.3459 g of sodium selenite in 20 mL of ultrapure water respectively, mix the three under stirring at room temperature after ultrasonic dispersion for 20 min; then slowly add an appropriate amount of alkali (such as sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium hydroxide) to the above solution to adjust the pH value to 13.0, continue stirring and slowly transfer to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction, and heat at 200 °C for 24 hours; after the reactants are cooled, filter them, wash with deionized water and ethanol, and dry them in an oven at 60 °C for 12 h to obtain the heterojunction composite material Cs3Bi2I9 / Bi2O2Se.
[0041] Figure 1 This is a scanning electron microscope image of Cs3Bi2I9 / Bi2O2Se prepared in this example. Figure 1 As shown, Cs3Bi2I9 nanoparticles are distributed on Bi2O2Se nanosheets. Loading Cs3Bi2I9 particles on the surface of Bi2O2Se material is expected to be more stable in the photoreaction, which is beneficial to improve the stability of the composite material in the aqueous phase.
[0042] Comparative Example 1
[0043] Only the catalyst Cs3Bi2I9 was prepared:
[0044] 1.2 mM BiI3 and 1.8 mM CsI were mixed in a round-bottom flask containing 15 mL (180 mM) N,N-dimethylformamide. The mixture was continuously heated at 60 °C under magnetic stirring at 600 r / min until the solvent was completely evaporated. It was then centrifuged and washed three times with toluene to remove the N,N-dimethylformamide residues. After drying in an oven at 60 °C for 12 h, bright red powder Cs3Bi2I9 was obtained.
[0045] Comparative Example 2
[0046] Only the catalyst Bi2O2Se was prepared:
[0047] 1.808 g of ammonium bismuth citrate and 0.3459 g of sodium selenite were dispersed in 20 mL of ultrapure water respectively, and the three were mixed under stirring at room temperature after ultrasonic dispersion for 20 min; then an appropriate amount of alkali (such as sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium hydroxide) was slowly added to the above solution to adjust the pH value to 13.0, and after continuous stirring, it was slowly transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction and heated at 200 °C for 24 hours; after the reactant was cooled, it was filtered, washed with deionized water and ethanol, and dried in an oven at 60 °C for 12 h to obtain the product Bi2O2Se.
[0048] Embodiment 2,
[0049] A method for synthesizing a halogen perovskite-based heterojunction composite material comprises the following steps:
[0050] A. Mix 0.2 mM BiI3 and 0.3 mM CsI in a round-bottom flask containing 1.25 mL (15 mM) N,N-dimethylformamide. Heat the mixture at 80 °C under magnetic stirring at 600 r / min until the solvent N,N-dimethylformamide is completely evaporated. Then, centrifuge and wash it three times with toluene to remove the N,N-dimethylformamide residue. Dry it in an oven at 80 °C for 24 h to obtain a bright red powder Cs3Bi2I9 for use.
[0051] B. Disperse 1.0 g of Cs3Bi2I9, 3.616 g of ammonium bismuth citrate and 0.6918 g of sodium selenite in 20 mL of ultrapure water respectively, mix the three under stirring at room temperature after ultrasonic dispersion for 20 min; then slowly add an appropriate amount of alkali (such as sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium hydroxide) to the above solution to adjust the pH value to 11.0, continue stirring and slowly transfer to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction, and heat at 180 °C for 20 hours; after the reactants are cooled, filter them, wash with deionized water and ethanol, and dry them in an oven at 80 °C for 24 h to obtain the heterojunction composite material Cs3Bi2I9 / Bi2O2Se.
[0052] Embodiment 3,
[0053] A method for synthesizing a halogen perovskite-based heterojunction composite material comprises the following steps:
[0054] A. Mix 1.0 mM BiI3 and 1.5 mM CsI in a round-bottom flask containing 25 mL (300 mM) N,N-dimethylformamide. Heat the mixture at 80 °C under magnetic stirring at 600 r / min until the solvent N,N-dimethylformamide is completely evaporated. Then, centrifuge and wash it three times with toluene to remove the N,N-dimethylformamide residue. Dry it in an oven at 70 °C for 18 h to obtain a bright red powder Cs3Bi2I9 for use.
[0055] B. Disperse 1.0 g of Cs3Bi2I9, 1.205 g of ammonium bismuth citrate and 0.2306 g of sodium selenite in 20 mL of ultrapure water respectively, mix the three under stirring at room temperature after ultrasonic dispersion for 20 min; then slowly add an appropriate amount of alkali (such as sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, ammonium hydroxide) to the above solution to adjust the pH value to 12.0, continue stirring and slowly transfer to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction, and heat at 180 °C for 24 hours; after the reactants are cooled, filter them, wash with deionized water and ethanol, and dry them in an oven at 60 °C for 12 h to obtain the heterojunction composite material Cs3Bi2I9 / Bi2O2Se.
[0056] 1. Evaluation of photocatalytic degradation performance
[0057] The photocatalytic degradation performance of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 was evaluated as follows:
[0058] The photodegradation experiments of atrazine were conducted to evaluate the photodegradation performance of the synthesized Cs3Bi2I9 / Bi2O2Se photocatalyst under PMS activation. The photodegradation process was carried out in a 250 mL custom-made double-walled quartz beaker with a cooling water circulation system to keep the reaction temperature constant. A 300 W xenon lamp (λ>420 nm) was used as a visible light source with an average light intensity of 200 mW / cm 2 . Before the reaction started, 50 mg of the photocatalyst was dispersed in atrazine solution (5 mg / L, 100 mL), and the pH was controlled at about 7 with 0.1 M hydrochloric acid or sodium hydroxide solution. The suspension was stirred continuously during the entire reaction. Dark adsorption experiments were performed 30 min before illumination to achieve the adsorption-desorption equilibrium between atrazine and the photocatalyst. Then, 1 mM PMS was added. During the photodegradation process, 1 mL of the reaction solution was taken out at regular intervals and then passed through a 0.22 μm filter. The concentration of atrazine (ATZ) was measured by HPLC (Shimadzu, LC-16) using an Agilent SB-C18 column (2.1 mm × 100 mm, 1.8 μm) with a UV detector at 225 nm. The mobile phase was methanol and ultrapure water in a volume ratio of 50:50. The relative concentration (C / C0) was used to calculate the degradation efficiency.
[0059] Figure 2 The UV diffuse reflectance spectra of Cs3Bi2I9 / Bi2O2Se, Cs3Bi2I9, and Bi2O2Se prepared in Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 2 As shown in the figure, Cs3Bi2I9 exhibits light absorption in the ultraviolet and visible light regions, with an absorption edge of ~654nm, which indicates that a single Cs3Bi2I9 cannot effectively utilize visible light in the range of 650-800nm. Bi2O2Se has strong absorption throughout the entire visible spectrum, and its spectral absorption is significantly enhanced compared to traditional BiOCl (light absorption cutoff edge is about 380nm) and BiOBr (light absorption cutoff edge is about 450nm). At the same time, for Cs3Bi2I9 / Bi2O2Se, it can be seen that the composite of Bi2O2Se effectively enhances the tail peak intensity of the material, indicating that the two form complementary light absorption, which is beneficial to improving the visible light capture efficiency.
[0060] Figure 3 Fourier diffuse reflectance infrared spectra of Cs3Bi2I9 / Bi2O2Se, Cs3Bi2I9, and Bi2O2Se prepared in Example 1 and Comparative Examples 1 and 2. For Cs3Bi2I9, at 1649 cm -1 There is an absorption peak at 1277cm -1 and 1108cm-1 The peak corresponds to the stretching vibration of the CO bond and is located at 3441 cm −1 The bands at 621 cm -1 The peak at 1674 cm -1 and 1476cm -1 The peak corresponds to the CO bond and is located at 3419 cm −1 The bands correspond to the deformation vibration of hydroxyl groups. At the same time, the main typical absorption peaks of the original Cs3Bi2I9 and Bi2O2Se are present in the Cs3Bi2I9 / Bi2O2Se sample, which further indicates the successful synthesis of the Cs3Bi2I9 / Bi2O2Se composite catalyst.
[0061] Figure 4 The performance comparison chart of photocatalytic degradation of atrazine by Cs3Bi2I9 / Bi2O2Se, Cs3Bi2I9 and Bi2O2Se prepared in Example 1 and Comparative Examples 1 and 2 is shown in FIG. Figure 4 As shown in the figure, the experimental results show that under the conditions of catalyst dosage of 0.5 g / L, initial atrazine concentration of 5 mg / L and initial temperature of room temperature, within 30 min, the degradation efficiency of atrazine by single Cs3Bi2I9 / PMS / Vis and Bi2O2Se / PMS / Vis systems was 7.55% and 40.44%, respectively, while the removal rate of atrazine by Cs3Bi2I9 / Bi2O2Se / PMS / Vis system reached 98.37%, which means that the composite material of selenium-mediated bismuth oxide and bismuth-based halide perovskite material makes use of more visible light, and the construction of Z-type heterojunction and interlayer electrostatic interaction effectively improve the interfacial charge transfer of photogenerated carriers and inhibit the in-situ recombination of photogenerated electron-hole pairs in two single photocatalysts.
[0062] 2. Continuous degradation experiment
[0063] After the first degradation reaction of the heterojunction composite material Cs3Bi2I9 / Bi2O2Se prepared in Example 1 is completed, the post-reaction solution is centrifuged and washed, and the recovered catalyst is dried in a freeze dryer for 48 h, and then put into the reactor again for the next degradation experiment. Except for the materials, the other degradation reaction conditions are consistent with the first photocatalytic degradation performance evaluation experiment setting procedure; after the second reaction is completed, the above steps are repeated to carry out three degradation experiments.
[0064] Figure 5 This is a degradation diagram of the reusability experiment of photocatalytic degradation of atrazine by Cs3Bi2I9 / Bi2O2Se prepared in Example 1. Figure 5As shown, the degradation efficiency of atrazine was above 90% in three consecutive degradation experiments, indicating that the photocatalytic activity of Cs3Bi2I9 / Bi2O2Se photocatalytic nanomaterials remained good after three cycles. This shows that anchoring bismuth-based halide perovskites on selenium-based bismuth oxide photocatalysts is beneficial to solving the instability problem of perovskite materials in aqueous phase.
[0065] Lead halide peroxides in the prior art show high solar energy collection efficiency. However, lead-based materials are toxic and unsuitable for wastewater treatment. In contrast, bismuth-based halide perovskites solve the stability and toxicity issues associated with lead-based materials. At the same time, compared with traditional bismuth oxyhalide materials, their visible light absorption is insufficient, while the valence band and conduction band characteristics in bismuth oxyselenide (Bi2O2Se) materials are mediated by selenium groups with different orbitals, which is conducive to improving the optical absorption of the material. Interlayer electrostatic interactions are conducive to accelerating the effective separation of photocarriers. Combining the two not only avoids the problem of instability of perovskite materials in aqueous phase, but also the presence of Bi2O2Se further improves the visible light absorption of the composite material. The electrostatic interaction and the constructed Z-type heterojunction promote the effective separation of photogenerated electron-hole pairs.
Claims
1. A method for synthesizing a halogen perovskite-based heterojunction composite material, characterized in that The following steps are involved: A. Mix BiI3 and CsI in N,N-dimethylformamide, heat the mixture under stirring until N,N-dimethylformamide is completely evaporated, remove the N,N-dimethylformamide residue, and dry to obtain Cs3Bi2I9 for later use; B. Disperse Cs3Bi2I9, ammonium bismuth citrate and sodium selenite in ultrapure water respectively, and mix the three under stirring at room temperature; then adjust the pH value to 11.0-13.0, and carry out hydrothermal reaction after continuous stirring. After the reactants are cooled, filter, wash and dry to obtain the heterojunction composite material Cs3Bi2I9 / Bi2O2Se.
2. The method for synthesizing a halogen perovskite-based heterojunction composite material according to claim 1, characterized in that: In step A, the ratio of the amounts of BiI3, CsI and N,N-dimethylformamide is 1-2:1.5-3:150-300.
3. The method for synthesizing a halogen perovskite-based heterojunction composite material according to claim 1, characterized in that: In step A, the heating temperature is 60-80°C.
4. The method for synthesizing a halogen perovskite-based heterojunction composite material according to claim 1, characterized in that: In step A, the drying temperature is 60-80°C and the drying time is 12-24 h.
5. The method for synthesizing a halogen perovskite-based heterojunction composite material according to claim 1, characterized in that: In step B, the mass ratio of Cs3Bi2I9, ammonium bismuth citrate and sodium selenite is 1:1.2-3.6:0.2-0.
7.
6. The method for synthesizing a halogen perovskite-based heterojunction composite material according to claim 1, characterized in that: In step B, the temperature of the hydrothermal reaction is 180-200° C., and the time of the hydrothermal reaction is 20-24 h.
7. The method for synthesizing a halogen perovskite-based heterojunction composite material according to claim 1, characterized in that: In step B, the drying temperature is 60-80°C and the drying time is 12-24 h.
8. A halogen perovskite-based heterojunction composite material, characterized in that: The halogen perovskite-based heterojunction composite material is prepared by the synthesis method of any one of claims 1 to 7.
9. Use of the halogen perovskite-based heterojunction composite material according to claim 8 in visible light photocatalytic degradation of pollutants in wastewater.
10. The use of a halogen perovskite-based heterojunction composite material according to claim 9 in visible light photocatalytic degradation of pollutants in wastewater, characterized in that: The pollutants in the wastewater include atrazine.
Citation Information
Patent Citations
Preparation method of bismuth oxyselenide nanosheets and heterojunction photoelectrode based on bismuth oxyselenide nanosheets
CN112588303A
Selenium bismuth oxide / silver phosphate nano composite material as well as preparation method and application thereof
CN116943693A
